2020
DOI: 10.7554/elife.49658
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore direct RNA sequencing maps the complexity of Arabidopsis mRNA processing and m6A modification

Abstract: Understanding genome organization and gene regulation requires insight into RNA transcription, processing and modification. We adapted nanopore direct RNA sequencing to examine RNA from a wild-type accession of the model plant Arabidopsis thaliana and a mutant defective in mRNA methylation (m6A). Here we show that m6A can be mapped in full-length mRNAs transcriptome-wide and reveal the combinatorial diversity of cap-associated transcription start sites, splicing events, poly(A) site choice and poly(A) tail len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

47
550
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(601 citation statements)
references
References 98 publications
47
550
4
Order By: Relevance
“…Another type of transcripts that we and other teams observed in hen2-2 and se-2 plants are truncated or misprocessed transcripts spanning the first intron (14,15,35,68). Similar 5′ transcript derived from protein coding genes have also been observed in human cells depleted from ARS2 and result from premature transcription termination rather than from compromised splicing of full-length pre-mRNAs (19,34,69).…”
Section: Discussionmentioning
confidence: 69%
“…Another type of transcripts that we and other teams observed in hen2-2 and se-2 plants are truncated or misprocessed transcripts spanning the first intron (14,15,35,68). Similar 5′ transcript derived from protein coding genes have also been observed in human cells depleted from ARS2 and result from premature transcription termination rather than from compromised splicing of full-length pre-mRNAs (19,34,69).…”
Section: Discussionmentioning
confidence: 69%
“…Direct RNA-Seq has been used to analyse m6A in yeast (Garalde et al 2018;H. Liu et al 2019) , Arabidopsis (Parker et al 2020) , RNA virus genomes (Kim et al 2020) and in human cells (Workman et al 2019;Leger et al 2019;Lorenz et al 2020) . Here we showed that differential RNA modifications can be identified across a larger number of genetically diverse human cancer cell lines.…”
mentioning
confidence: 99%
“…Given the recent discovery of numerous novel functional transcripts in multiple organs (3,58), the re-evaluation of transcript diversity and complexity in model organisms (4,5,59,60) and the growing interest in Oxford Nanopore direct-RNA multiple assets in viral transcriptome research (61-64), TALC's capacity to correct the entire gamut of transcripts, and preserve the correct transcript structure may prove increasingly valuable. Table 1: Usual alignment-based statistics for the 7 correction methods tested: primary alignment rates and base accuracy (real LR data corrected by real SR data).…”
Section: Discussionmentioning
confidence: 99%